1974
DOI: 10.1073/pnas.71.6.2337
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enhancement of Chick Intestinal DNA-Dependent RNA Polymerase II Activity by 1α,25-Dihydroxyvitamin D 3 , In Vivo

Abstract: la,25-dihydroxyvitamin D3 was examined for its ability to affect the DNA-dependent RNA polymerases (nucleosidetriphosphate:RNA nucleotidyltransferase, EC 2.7.7.6) of rachitic chick intestinal cell nuclei in vivo. Nucleoplasmic (form II) RNA polymerase activity was stimulated 2-fold (P < 0.05) within 2-3 hr after an oral dose of 0.27 sAg (0.65 nmol) of la,25-dihydroxyvitamin D3 to rachitic chicks. The form II polymerase activity returned to control values by 5-9 hr after dosing with the sterol. In contrast, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…3). Yet the amount of hormone accumulated in the nucleus (Lawson & Emtage, 1974), together with the increased RNA polymerase II activity (Zerwekh et al, 1974), are maximal within 2h. In other systems, newly transcribed mRNA is processed very rapidly, with a halflife of minutes, into mature mRNA (Curtis & Weissmann, 1976;Bastos & Aviv, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Yet the amount of hormone accumulated in the nucleus (Lawson & Emtage, 1974), together with the increased RNA polymerase II activity (Zerwekh et al, 1974), are maximal within 2h. In other systems, newly transcribed mRNA is processed very rapidly, with a halflife of minutes, into mature mRNA (Curtis & Weissmann, 1976;Bastos & Aviv, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that after the rapid accumulation of the hormone in chick intestinal nuclei (Lawson & Emtage, 1974) nuclear RNA synthesis is stimulated (Tsai & Norman, 1973), as is RNA polymerase activity (Zerwekh et al, 1974) and DNA template capacity (Zerwekh et al, 1976), and the physiological response is inhibited in vitro by a-amanitin and actinomycin D (Corradino, 1973). Thus RNA transcription and protein synthesis were implicated in the mechanism ofaction ofthe hormone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION A wide variety of hormones administered in vivo have been reported to result in enhanced chromatin-bound or nuclear RNA polymerase in both plants (3,13,14) and animals (15)(16)(17)(18). Both nucleolar (17,18) and nucleoplasmic (19) RNA polymerases are subject to hormonal regulation in animals. The nucleolar RNA polymerase (RNA polymerase I) transcribes ribosomal RNA (20,6), while the nucleoplasmic RNA polymerase (RNA polymerase II) is thought to transcribe messenger RNA (21).…”
mentioning
confidence: 99%
“…It is known, for example, that 1,25-(OH)2D3 is rapidly localized to the nucleus of intestinal cells (4)(5)(6)(7)(8). In all likelihood, 1,25-(OH)2D3 enters the cell and associates with a cytosolic binding protein (9,10) prior to translocation into the nucleus (11). In the nucleus it increases RNA polymerase II activity (11), RNA synthesis (12), chromatin template activity (13), and the synthesis of mRNA for calcium-binding protein (14).…”
mentioning
confidence: 99%